Pengaruh Kepemimpinan Transformasional dan Kompensasi terhadap Loyalitas Karyawan di Bank bjb Syariah KCP Majalaya - Dewi Ratu Fitriana; Faisal Rakhman; Dadang Dimyati (Ma'soem University, 2021)
The results of this study indicate that there is no significant influence between transformational leadership on employee loyalty at Bank BJB Syariah KCP Majalaya, with the results of the t-test where the value of tcount > ttabel (8,111 > 2,160), there is a significant effect between compensation on employee loyalty at Bank BJB Syariah KCP Majalaya with the result of the t-test where the value of tcount > ttabel (6,460 > 2,160) and simultaneously there is a significant influence between transformational leadership and compensation on employee loyalty with the result of the F-test, namely Fcount > Ftabel (32,302 > 3,74).